Systemetic Literature Review : Pengaruh Effleurage Massage terhadap Nyeri Persalinan - Alvin Alvani Tresna Ambari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Childbirth is a natural process, this process, although natural, is often accompanied by quite intense pain, especially in the first stage of labor. Pain in the first stage of labor can have a significant psychological and physical impact on the mother. (1) The Indonesian Hospital Association Data Center explains that 15% of mothers in Indonesia experience labor complications and 21% state that the labor they experience is a painful labor because they feel very painful, while 63% do not receive information about the preparations that must be made to reduce pain during labor. One non-pharmacological approach that can be applied in labor pain management is the effleurage massage technique. Effleurage massage is a light massage technique with stroking movements that can provide relaxation to tense muscles, relieve physical and emotional tension, and reduce pain perception. The application of this technique is expected to have a positive impact on the level of intranatal maternal comfort during the first stage of labor. (2) The purpose of this literature review research is to determine the technique of reducing labor pain. The research method used is a literature review. Article searches were carried out on Google Scholar and Pubmed with the keywords techniques for reducing labor pain. The selected articles are Indonesian and English articles published from 2018 to 2024 in 5 journals that can be accessed in full text in pdf format. The results of the study showed that there was an effect of effleurage massage on labor pain.